Comparison of the new miniature Wright peak flow meter with the standard Wright peak flow meter. Issue 6 (December 1979) - Oldham, H G; Bevan, M M; McDermott, M
Abstract : Preproduction and current models of the miniature Wright peak flow meter have been compared with the standard Wright peak flow meter on normal and abnormal subjects. Early problems in production appear to have been overcome, and the current model agrees to within 3% with the standard peak flow meter, which is as close as the agreement between two standard instruments. The new mini-meter may be enclosed in a case, making direct comparisons with other instruments possible.